The Effect of Social Support on Athlete Burnout in Weightlifters: The Mediation Effect of Mental Toughness and Sports Motivation - Shang, Yao; Yang, Shi-Yong (Frontiers in Psychology, 2021)
Objectives: Athlete burnout is a crucial concern affecting the development and athletic performance of young weightlifters. To reduce or relieve the prevalence of athlete burnout. This study examined the relationship across social support, sports motivation, mental toughness, and athlete burnout in weightlifters. Method: A total of 315 weightlifters aged 17 to 28 years old (151 males,164 females; M age=16.89 yrs, SD=3.66) from Sichuan, Chongqing, and Shanxi in China participated in this survey. Perceived Available Support in Sport Questionnaire (PASS-Q), Sports Motivation Questionnaire (SMQ), Sports Mental Toughness Questionnaire (SMTQ), and Athlete Burnout Questionnaire (ABQ) were used in this study. SPSS Statistics 19.0, AMOS 21. 0, and PROCESS 3.0 Macro were used to analyze the survey data. Results: The results indicated that weightlifters' social support could negatively significantly affect athlete burnout (beta=-0.398 (95% confidence interval (CI): [-0.3699, -0.2184], p<0.05) via mental toughness and sports motivation. The mediation analysis revealed that it had partial mediating effect, which consisting of three paths: First, social support had direct effect on athlete burnout (beta=-0.150, 95% CI: [-0.1824, -0.0397], p<0.05). Second, sport mental toughness had mediating effect on athlete burnout (beta=-0.113, 95% CI: [-0.1703, -0.0631], p<0.05). Finally, sports motivation had mediating effect on athlete burnout (beta=-0.124, 95% CI: [-0.1751, -0.0793], p<0.05). Conclusion: The present study revealed that social support can inhibit or prevent athlete burnout via mental toughness and sports motivation, thus, to decrease or relieve the prevalence of burnout in weightlifter, it is an important solution to enhance their social support.